2018
DOI: 10.3389/fpsyg.2018.01390
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Inattentional Blindness Does Not Always Decrease With Age

Abstract: Children usually miss additional information when they focus on objects or events. This common phenomenon is termed as inattentional blindness. To explore the age-related degree of this phenomenon, we applied a motion task to study the developmental difference of inattentional blindness. A group of 7-to-14-year-old children and adults participated in Experiment 1. The results showed that there was no significant developmental difference in sustained inattentional blindness. Considering that young children’s pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Of course, this cannot be generalized to the load literature more broadly, as it was only evaluated within studies employing a static search array task (e.g., Calvillo & Jackson, 2014). It is an open question whether this finding holds for studies that have used more disparate methods of manipulating load (Zhang et al, 2018). Nevertheless, this subset of studies seems a good starting place for an understanding of the validity of comparing differential load effects across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, this cannot be generalized to the load literature more broadly, as it was only evaluated within studies employing a static search array task (e.g., Calvillo & Jackson, 2014). It is an open question whether this finding holds for studies that have used more disparate methods of manipulating load (Zhang et al, 2018). Nevertheless, this subset of studies seems a good starting place for an understanding of the validity of comparing differential load effects across studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the dynamics of the task could be critical given that some tasks, like the "gorilla-task" of Simons and Chabris (1999), involve motion and very distinctive IB stimuli while other tasks are static and use less prominent IB-stimuli (e.g., Buetti et al, 2014). Indeed, some contradictory results have been found, using different dynamic/static tasks (Memmert, 2014;Zhang et al, 2018). Dynamic stimuli do not necessarily generate IB in the same manner as the static stimuli used here, especially in children (for instance, a word can attract more attention than a letter, as we have seen in the results for our older 9+ observers).…”
Section: The Inattentional Blindness E Ect To Study Attentional Proce...mentioning
confidence: 99%
“…At the other end of the lifespan continuum, using the gorilla paradigm, Memmert (2014) found that younger children were more likely to show IB effects in a large sample of 480 participants from 8 to 15 years-old. However, Zhang et al (2018) failed to find that effect in their sample of 210 observers from 7 to 14 years-old, using a T among L's dynamic IB-task based on Most et al (2001). Zhang et al (2019) also tested 3 to 5 years-old observers in Mack and Rock's (1998) original "cross judging" IB paradigm.…”
Section: Introductionmentioning
confidence: 97%